Guideline adherence in ovarian cancer for surgical staging in the Netherlands. Issue 12 (21st October 2022) - Baldewpersad Tewarie, Nishita M S; van Ham, Maaike; Wouters, Michel; Kruitwagen, Roy; van Driel, Willemien
Abstract : Objective: Previous studies have shown low adherence to surgical staging guidelines in patients with clinical early-stage ovarian carcinoma. The aim of this study was to identify guideline adherence for surgical staging and to show the distribution of each surgical item within the study population. In addition, we examined whether regional variation in the Netherlands exists for complete surgical staging. Methods: Patients with ovarian cancer and surgical staging registered in the Dutch Gynecological Oncology Audit between January 1, 2015 and December 31, 2019 in the Netherlands were included. Complete surgical staging was defined according to the Dutch evidence-based guideline. Surgical items were ranked and illustrated. Variation in complete surgical staging for eight regional cancer networks was shown in funnel plots. Manual validation of registered data was performed in three gynecological oncology centers. Results: 604 patients underwent surgical staging, 365 (60%) underwent an incomplete staging procedure, 295 (81%) were registered with early-stage disease (International Federation of Gynecology and Obstetrics I–IIA) and, of these patients, 115 (39%) received adjuvant chemotherapy. Patients with incomplete surgical staging were operated more often with minimal invasive techniques (laparoscopy or robot) compared with patients in the complete staging group (p<0.001). Sampling of cytology/ascites was the most frequently lacking factor (29%). Manual validation of data in three gynecological oncology centers identified reasons for incomplete staging, the most common being 'perioperative findings' such as dense adhesions between tumor and peritoneum, consistent with advanced stage disease (≥IIA). Regional variation for complete surgical staging showed two regions performing outside the confidence intervals (12.5% and 25.5%, mean 40%). Conclusion: Guideline adherence for staging was lower than expected and validation of data gave additional insights into the reasons that were contributing to incomplete surgical staging. Moreover, this analysis showed that regional variation for surgical staging exists, which forms a starting point to improve and harmonize staging procedures for these patients nationwide.